Surface Functionalization of Three Dimensional-Printed Polycaprolactone-Bioactive Glass Scaffolds by Grafting GelMA Under UV Irradiation - Ghorbani, Farnaz; Sahranavard, Melika; Mousavi Nejad, Zohre; Li, Dejian; Zamanian, Ali; Yu, Baoqing (Frontiers in Materials, 2020)
In this study, bioactive glass nanoparticles (BGNPs) with an average diameter of less than 10 nm were synthesized using sol-gel method and then characterized by transmission electron microscopy (TEM), differential scanning calorimetric (DSC), Fourier transforms infrared spectroscopy (FTIR), and X-Ray spectroscopy (XRD). Afterward, three dimensional (3D)-printed polycaprolactone (PCL) scaffolds along with fused deposition modeling (FDM) were incorporated with BGNPs, and the surface of composite constructs was then functionalized by coating with the gelatin methacryloyl (GelMA) under UV irradiation. Field emission scanning electron microscopy micrographs demonstrated the interconnected porous microstructure with an average pore diameter of 260 µm and homogeneous distribution of BGNPs. Therefore, no noticeable shrinkage was observed in 3D-printed scaffolds compared with the computer-designed file. Besides, the surface was uniformly covered by GelMA, and no effect of surface modification had been observed on microstructure while surface roughness increasing. The addition of BGNPs to PCL scaffolds showed a slight change in pore size and porosity; however, it increased surface roughness. According to mechanical analysis, the compression strength of scaffolds increased by the BGNPs addition and surface modification. Also, a reduction was observed in absorption capacity and biodegradation of scaffolds in phosphate-buffered saline media after incorporation of BGNPs, while the presence of the GelMA layer increased the swelling potential and stability of composite matrixes. Moreover, the capability of inducing bio-mineralization of hydroxyapatite-like layers, as a function of BGNPs content, was proved by FE-SEM micrographs, EDX spectra, and X-Ray diffraction spectra (XRD) after soaking the obtained samples in the concentrated simulated body fluid. A higher potential of the modified constructs to interact with aqueous media led to better precipitation of minerals. According to in-vitro assays, the modified scaffolds can provide a suitable surface for the attachment and spreading of the bone marrow mesenchymal stem cells (BMSCs). Furthermore, the number of the proliferated cells confirms the biocompatibility of scaffolds, especially after a modification process. Cell differentiation was verified by alkaline phosphatase activity as well as the expression of osteogenic genes such as osteocalcin and osteopontin. Accordingly, scaffolds showed an initial potential for reconstruction of the injured bone.